2017
DOI: 10.1007/s00204-017-2092-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute regulation of multidrug resistance-associated protein 2 localization and activity by cAMP and estradiol-17β-d-glucuronide in rat intestine and Caco-2 cells

Abstract: Multidrug resistance-associated protein 2 (MRP2) is an ATP-dependent transporter expressed at the brush border membrane of the enterocyte that confers protection against absorption of toxicants from foods or bile. Acute, short-term regulation of intestinal MRP2 activity involving changes in its apical membrane localization was poorly explored. We evaluated the effects of dibutyryl-cAMP (db-cAMP), a permeable analog of cAMP, and estradiol-17β-D-glucuronide (E17G), an endogenous derivative of estradiol, on MRP2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
(72 reference statements)
2
10
1
Order By: Relevance
“…We also found that PKA participation is necessary to explain, at least in part, modulation of MRP2 activity by adenosine (Figure 3). These findings agree with previous evidence in hepatic and intestinal models demonstrating the ability of cAMP/PKA axis to acutely increase MRP2 activity 22,51 . However, it is important to note that cAMP increase not only leads to PKA activation, but can also increase the activity of other kinases such as exchange protein directly activated by cAMP, phosphoinositide 3‐kinase or p38 mitogen‐activated protein kinases, all of them also able to acutely modulate MRP2 localization in hepatic models 51 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We also found that PKA participation is necessary to explain, at least in part, modulation of MRP2 activity by adenosine (Figure 3). These findings agree with previous evidence in hepatic and intestinal models demonstrating the ability of cAMP/PKA axis to acutely increase MRP2 activity 22,51 . However, it is important to note that cAMP increase not only leads to PKA activation, but can also increase the activity of other kinases such as exchange protein directly activated by cAMP, phosphoinositide 3‐kinase or p38 mitogen‐activated protein kinases, all of them also able to acutely modulate MRP2 localization in hepatic models 51 .…”
Section: Discussionsupporting
confidence: 91%
“…Thus, Caco‐2 cell monolayers grown on permeable supports constitute an optimal in vitro model system for drug transport studies 40 . In addition, using confocal microscopy and membrane fractionation followed by immunoblotting studies, rapid changes in MRP2 localization were already confirmed in these cells 22 . In the current work, we demonstrated that acute treatment with adenosine led to a significant increase in MRP2 activity (Figure 3B) which was associated with apical insertion of the transporter (Figure 4).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations